A Literature Review on Current Application of Artificial Intelligence Technology in Medical Devices Manufacturing - Putro, Bayu Suryo; Nugrah, Evans Afriant; Maulana, Galuh; Achsan, Harry Tursulistyono Yani (Multidiscience : Journal of Multidisciplinary Science, 2025)
The medical device industry is currently an industry with very high growth in Indonesia. The growth of this manufacturing industry must be accompanied by the development of aspects in it along with the industrial revolution 5.0. Manufacturing and quality assurance are essential aspects of the medical device industry. They have a substantial impact on the safety, efficacy, and adherence to strict regulations of products. This systematic literature review aims to provide a discusses the critical role of AI in optimizing aspects of quality control and quality assurance in the medical device industry. In manufacturing, AI optimizes quality control through AI-enabled inspection systems that can detect microscopic defects and ensure compliance with stringent regulatory standards. The visual inspection process utilizes AI technology via computer vision and machine learning. In addition, automation of documentation processes for regulatory compliance by performing complex analysis and tasks involving large amounts of regulatory data. AI-based technology has revolutionized medical device manufacturing by enhancing quality control. However, challenges remain for its swift implementation in Indonesia, including issues with data availability and accuracy. It is anticipated that this issue will be resolved promptly to enable the swift implementation of this AI-based technology in Indonesia.